An evaluation of English e-book ‘Think Globally Act Locally’ for the ninth graders - Sri Meiweni Basra (Journal on English as a Foreign Language, 2018)
This research investigated whether the 2013 curriculum English electronic book (e-book) ‘Think Globally Act Locally’ was categorized as a good quality e-book and how the e-book represented the criteria of a good quality e-book. By using the principle of qualitative research, a criteria checklist was used as the research instrument. The result showed that the e-book met 59% out of 66 criteria of a good quality e-book. The strengths of the e-book were in terms of the relation between the content provided and students’ real-life situation, amount of exposure of speaking skills and grammar, and its appealing physical appearance. However, drawbacks such as failures to promote target culture learning, to expose language skills and sub-skills equally and to accommodate supplementary materials and digital features were found. The findings of the research showed that improvements toward the e-book should be made. Hopefully, this research provides insights for e-book writers to create more improved e-books by meeting the criteria of a good e-book and for English teachers to be effective in using learning materials.